Evaluation of Combination Fungicides for Charcoal Rot and Collar Rot Management in Soybean - Laxman Singh Rajput; Mohammad Samio Shaikh; Munmi Borah; Sanjeev Kumar; Vennampally Nataraj; Maranna Shivakumar; Hemant Singh Maheshwari; Kriti Pathak; Aman Gupta; Divyanshu Goswami; Pinnamwar Keerthi; Sumit Kumar; et al. (Agronomy)
Soil-borne diseases, including charcoal rot (Macrophomina phaseolina) and collar rot (Sclerotium rolfsii), threaten global soybean production. Four fungicide combinations were tested as seed treatments at three concentrations (1, 1.5, and 2 g or ml per kg of seed) under controlled conditions to address the challenges posed by these diseases. Under controlled conditions, the combination of thiophanate methyl + pyraclostrobin at a rate of 2 mL/kg of seed significantly alleviated disease symptoms caused by both pathogens. Additionally, it enhanced shoot and root weights by over 50% in plants affected by S. rolfsii. Field trials were conducted for two years at two distinct locations to assess the efficacy of three selected combination seed treatment fungicides against M. phaseolina and S. rolfsii. Both inoculated and uninoculated controls were included for the comparison. Among the fungicides, thiophanate-methyl + pyraclostrobin and trifloxystrobin + penflufen proved the most effective for suppressing both diseases under epiphytotic field conditions across the years and locations. This study also highlighted the benefits of these chemical combinations in enhancing agronomic traits, maintaining yield, and ensuring the economic viability of soybeans.